Dinamika Pertumbuhan Ekonomi Ibu Kota Negara (IKN): Peran Indeks Kemahalan Konstruksi, Tingkat Pengangguran, dan Investasi - Amalia, Meby; Indirman, Veri; Valdiansyah, Riyan Harbi (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2025)
This study aims to analyze the effect of the construction cost index and unemployment rate on regional economic growth, with the investment rate as an intervening variable. This study uses data from the National Capital City (IKN) for the 2019-2023 period using panel data from 10 cities in the IKN region for five years. This study used path analysis (mediation) with the Sobel test. The results show a significant relationship between the construction cost index and unemployment rate and economic growth. Construction infrastructure investment has a long-term positive impact through improved infrastructure quality and job creation. On the other hand, a high unemployment rate can hamper economic growth because of decreased purchasing power and limited market demand. This research emphasizes the importance of careful and sustainable infrastructure development planning as well as efforts to create quality jobs to support inclusive economic growth. The results provide important insights for policymakers and developers in planning infrastructure development in IKN.